KEWENANGAN MAHKAMAH AGUNG REPUBLIK INDONESIA DALAM PEMBUATAN PERATURAN TENTANG PERMOHONAN PERNYATAAN PAILIT MELALUI SURAT EDARAN (BELEIDSREGELS) DITINJAU DARI SUDUT ILMU PERUNDANG-UNDANGAN - Samuel Tirta Handoyo; Cut Memi (Jurnal Hukum Adigama, 2019)
One important element of the rule of law is that any government action must be based on law. The consequence is that laws must be made, implemented and enforced. Therefore, the state has the power to make laws to regulate all its activities. The Supreme Court as one of the highest judicial institutions in Indonesia has the status of all the courts and as the highest court for the four judicial institutions. The regulating and oversight functions are part of the functions of the Supreme Court, where the Supreme Court is authorized to issue further regulations in the form of Supreme Court Regulations and Supreme Court Circular Letters, where Supreme Court Regulations are regulating, whereas Supreme Court Circular Letters are as policy regulations. However, in practice the substance of the Supreme Court Circular is often not in accordance with its requirements, namely as a policy regulation. One of them is the Supreme Court Circular Letter Number 2 Year 2016 concerning Increasing Efficiency and Transparency in Handling Bankruptcy Cases and Delaying Obligations of Debt Payment in Courts. The writing of this thesis will discuss the authority of the Supreme Court in determining the substance of the Supreme Court Circular Number 2 of 2016 in terms of statutory knowledge. Judging from its nature, the research used is descriptive analysis using normative legal research.